The Equational Theory of Fixed Points with Applications to Generalized Language Theory - Ésik, Zoltán (BRICS Report Series, 2001)
We review the rudiments of the equational logic of (least) fixed points and provide some of its applications for axiomatization problems with respect to regular languages, tree languages, and synchronization trees.